Struggle of Legal Positivism Versus Progressive Thoughts in the Formal Tests of the Job Creation Act (Legal Development through Hermeneutics) - Imam Asmarudin (Jurnal Dinamika Hukum, 2022)
Hermeneutics is a form of interpretation and interpretation of a text in legal philosophy, in practice it is also used in the considerations of constitutional judges to interpret and interpret a law, one of which is in the formal examination of the work copyright law which is the pros and cons because using the Omnibus Law method. This study aims to find out how the struggle between positivistic and progressive legal thinking and the reality of the art of hermeneutics as a means of legal development, the research method uses the legal research method through the statute approach, conceptual approach, and case approach, the data analysis is descriptive qualitative, the research results show The struggles of Legal Positivism and Progressive Thought in the decision actually met at one point, both of them acknowledged that Omnibus Law was a method of future legislation formation and interpretation through the art of Hermeneutics became a means of making a legal construction, which in the end could become a means of developing law forward.Keywords: hermeneutics; legal positivism; omnibus law; progressive